The effect of systematic auditory stimuli micro-refresh on intellectual work performance and subjective measurement - Orchida Dianita; Takuto Higashimaki; Reika Abe; Kimi Ueda; Hirotake Ishii; Hiroshi Shimoda; Fumiaki Obayashi (Results in Engineering)
This study investigates the effect of auditory stimuli incorporated as a micro-refresh promoter during intellectual work by considering performance indicators and subjective measurement. A controlled laboratory experiment study was conducted with 47 participants performing a cognitive task under the conditions with and without auditory stimuli intervention. After data cleansing, 25 participants data were included in the analysis. Quantitative measurement of answering time and concentration time ratio resulted in no significant difference between conditions with and without auditory stimuli. Subjective ratings of NASA-TLX, subjective symptoms, and detachment factor found no significant difference among conditions with and without auditory stimuli. The recovery subjective questionnaire resulted in a significant difference in which participants felt more recovered when performing the task in auditory stimuli intervention. Regardless there are no statistically significant differences in several measurement indicators, there is a subjective indicator that auditory stimuli have an effect on intellectual work performance and it is worth considering for further research.